An outbreak of bovine tuberculosis in a fallow deer herd (Dama dama) in Sicily. (June 2016) - Amato, Benedetta; Mignacca, Sebastian Alessandro; Pacciarini, Maria Lodovica; Vitale, Maria; Antoci, Salvatore; Cucinotta, Salvatore; Puleio, Roberto; Biasibetti, Elena; Fiasconaro, Michele; Capucchio, Maria Teresa; Di Marco Lo Presti, Vincenzo
Abstract: Wild ruminants have an important role in the epidemiology of bovine tuberculosis (bTB). This study describes an outbreak of bovine tuberculosis occurring in a fallow deer herd in Sicily. In 2012 a Sicilian herd of 47 animals was referred for cachexia. Pathological examination of 2 dead animals revealed disseminated granulomas predominantly involving the skin and subcutaneous tissues. Tissue samples were submitted for histological analysis, bacteriological culture, and biomolecular assay. PCR analysis identified Mycobacterium strains. Genotyping by spoligotyping and MIRU-VNTR profiles identified Mycobacterium bovis spoligotype SB0120 in both animals. In 2014, bTB skin testing of 28 fallow deer from the same group was positive in 4 and inconclusive in another 4. All 8 positive/inconclusive reactors were euthanized. Disseminated granulomatous lesions were noted in 6 of these animals, 3 of which (2 positive and 1 negative to skin tests) also presented cutaneous lesions. M. bovis spoligotype SB0120 was identified from all animals in which tuberculous-like lesions were observed, including 2 negative reactors. Many of the animals involved in this outbreak presented diffuse skin lesions, a potential route of transmission of M. bovis infection. Given the epidemiological role wildlife play in the maintenance of bTB infection and its potential risk for humans, a comprehensive monitoring plan for this zoonosis in wildlife species in Sicily is needed. Highlights: Report of a case of bovine tuberculosis in a fallow-deer herd in Sicily, Italy Description of lesions involved by both in skin and organs Histological, bacteriological and biomolecular investigations are reported A relevant role of fallow deer in bovine tuberculosis epidemiology is suggested Public health concern for skin lesions as a mode of bovine tuberculosis spread